Comparing monetary policy rules in a small open economy framework: An empirical analysis using Bayesian techniques - Sabine Eschenhof (Technische Universität Darmstadt, Department of Law and Economics, 2009)
This paper examines the role of exchange rate changes in the monetary policy for the Euro Area. Moreover, it compares different Taylor-type policy rules with respect to the numerical results as well as the impulse responses to exogenous shocks and the fit of the different data model specifications when using the underlying data. Overall, a monetary policy rule which includes the expected inflation rate as well as the output gap performs best and supports a possible role of exchange rate changes in the Euro Area's monetary policy.
Keywords: C11; E52; F41; 330; Bayesian Estimation; Small Open Economy; Monetary Policy; Taylor Rule; Geldpolitik; Taylor-Regel; Europäische Wirtschafts- und Währungsunion; Kleines-offenes-Land; Bayes-Statistik; Schätzung; Eurozone